A performance of radio frequency and signal strength of LoRa with BME280 sensor - Puput Dani Prasetyo Adi; Akio Kitagawa (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
LoRa is a Radio Frequency module that can send packet data up to 3 km in FSPL.LoRa has 3 different Frequency Radios i.e, 915 MHz, 868 MHz, and 433 MHz. LoRa testing is based on different distances, BME280 provides Barometric Pressure, Temperature, and Humidity data. An analysis from the results of the Received Signal Strength to the distance (m) to the farthest point to prove and provide QoS data from LoRa 915 MHz. Sensor nodes are built using ADR and Automatic sleep mode algorithms. Communication systems between nodes are built dynamic sensor nodes in mesh networking. Monitoring signal transferring on the 915 MHz Frequency waveform is carried out using the Textronix Spectrum analyzer. Based on the BME280 Data packet transmission from the LoRa 915 MHz Transmitter to the Receiver Receiver at a distance of 100m is -84 dBm and at a distance of 500m is -107 dBm. The LoRa Internet Gateway has 2 types of settings, i.e, application, and gateway, this setting is to find out the location of the gateway with longitude and latitude. Furthermore, the gateway holds Sensor data from the End node, while the Application Server displays sensor data in the form of Graphics in realtime.